METABOLIC RESPONSE DURING HIGH-INTENSITY INTERVAL EXERCISE AND RESTING VASCULAR AND MITOCHONDRIAL FUNCTION IN CROSSFIT PARTICIPANTS (Kinesiology, 2023)
High-intensity functional training (HIFT) can play a major role in preventing cardiometabolic disease. The majority of HIFT interventions incorporate CrossFit (CF) training. We measured aerobic capacity, metabolic response during high-intensity interval exercise (HIIE), resting mitochondrial oxidative capacity, and resting vascular function in adults who participated in CF training (> one year) vs. a sedentary group completing one year (SED). Twenty-one participants were recruited (CF n = 13 vs. SED n = 8). CF participants had a 33.0% greater relative VO2 peak (p